Mutational burden and chromosomal aneuploidy synergistically predict survival from radiotherapy in non-small cell lung cancer - Qingzhu Jia (Nature Portfolio, 2021)
Here, the authors use whole exome sequencing to determine the effect of tumor mutational burden (TMB) and chromosomal aneuploidy (ANE) on survival outcomes of non-small cell lung cancer patients undergoing radiotherapy. The authors find that a higher TMB and lower ANE were correlated with better survival outcomes and that these factors interact synergistically.